2019
DOI: 10.1007/s40123-019-00205-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Azithromycin, Levofloxacin, and Ofloxacin in Rabbit Extraocular Tissues After Ophthalmic Administration

Abstract: IntroductionAzithromycin demonstrates high tissue distribution and prolonged elimination half-life. In this study, we monitored the pharmacokinetics of a single ophthalmic administration of 1% azithromycin ophthalmic solution containing polycarbophil in the extraocular tissues, including the eyelid, and compared it with that of two commercial ophthalmic products, 1.5% levofloxacin ophthalmic solution and 0.3% ofloxacin ophthalmic ointment.MethodsRabbits were treated with either a single topical administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For 1% azithromycin ophthalmic solution containing polycarbophil, availability was confirmed in the ocular tissues of rabbits, including tears, conjunctiva, and cornea. With a single drop of 1% azithromycin, the concentrations were sustained near the observed maximum levels for up to 24 hours post‐administration in all ocular tissue 14–16 . Similarly, following the instillation of a single drop of azithromycin eye drops in healthy volunteers, the mean tear concentration of azithromycin remained above the minimum inhibitory concentration for 24 hours 5,6 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For 1% azithromycin ophthalmic solution containing polycarbophil, availability was confirmed in the ocular tissues of rabbits, including tears, conjunctiva, and cornea. With a single drop of 1% azithromycin, the concentrations were sustained near the observed maximum levels for up to 24 hours post‐administration in all ocular tissue 14–16 . Similarly, following the instillation of a single drop of azithromycin eye drops in healthy volunteers, the mean tear concentration of azithromycin remained above the minimum inhibitory concentration for 24 hours 5,6 .…”
Section: Discussionmentioning
confidence: 88%
“…With a single drop of 1% azithromycin, the concentrations were sustained near the observed maximum levels for up to 24 hours post-administration in all ocular tissue. [14][15][16] Similarly, following the instillation of a single drop of azithromycin eye drops in healthy volunteers, the mean AUC 0-∞ , area under the curve from time zero to infinity; AUC 0-t , area under the curve from time zero to the specified time; CI, confidence intervall C max , peak concentration. Data are expressed as mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find direct evidence for the superiority of azithromycin eye drops over ointment, the results of animal studies comparing an eye drop formulation with eye ointment reported that the eye drop formulation is likely to be more effective for the treatment of a keratitis than an ointment because corneal penetration of the eye drops was better. 14,15 Oral linezolid was chosen based on the result of the in vitro susceptibility of the Pythium culture isolates where it fared well for the largest zone of inhibition, low minimum inhibitory concentration value, 7 and high concentrations achieved in aqueous and vitreous. 16 The analysis of clinical features of the infiltrate revealed midstromal tentacles (47.61%) and dot-shaped infiltrates (71.42%) as a frequent feature.…”
Section: Discussionmentioning
confidence: 99%